New Bio-Therapeutic Candidate for Pancreatic Cancer - Marwah Saad Joudah1, Basma Talib Al-Sudani2, Inam Sameh Arif1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
SIRT1 is NAD+-deacetylases, several histone and non-histone proteins which their involvement in metabolic processes, cell growth, apoptosis, and senescence are well known. Several Sirtuins targets are implicated in cancer. SIRT1 is both an oncogene and tumour suppressor, and it can act in this capacity depending on the kind of tissue and the cancer etiology. Subsequent studies in this field are going to make evident the exact function of SIRT1 at the cancer site and it is hoped that new chemotherapeutic functions of SIRT1 activators are going to be determined. In accordance with this, it is suggested that very selective ligands such as aptamer was created and investigated in various pancreatic cancer cell lines for the regulated activity of SIRT1. This study seeks to establish the therapeutic impact of the activator SIRT1 aptamer as a pharmacological model of pancreatic cancer by evaluating the impacts of activators SIRT1 (aptamer) on the growth of a series of human pancreatic cancer cell lines (AsPC-1, Capan-2, BxPC-3). Results gotten from in vitro cytotoxicity assays revealed that circular aptamer BAS inhibited the growth of pancreatic cancer cell lines [BxPc-3 (80%), Capan-2 (83%) and Aspc-1 (82.8%)] at 72h with IC50 0.55, 0.5, 0.76 ?M respectively. Importantly, circular aptamer showed no reduction of cell viability on the non- pancreatic cancerous H6c7 cell line, implying it might be safe to non-cancerous tissue. Our results indicate that the SIRT1 activated by aptamer could a promising targeted therapeutic approach for pancreatic cancer.